Faith and the nullity of marriage - Leszczyński, Grzgorz (Prawo Kanoniczne, 2022)
Marriage is a sacrament when it is concluded between two baptized persons. Does this mean, then, that it does not really matter in what disposition a given person gets married and that the fact of practicing the faith has no meaning whatsoever in relation to the validity of the marriage? Contemporary jurisprudence quite clearly defines the sacramentality of marriage in isolation from the fact of having faith and the intention to celebrate a sacramental marriage. Of course, from a pastoral point of view, deepening the faith should be a condition for contracting marriage. Moreover, a lack of faith certainly prevents the full enjoyment of the fruits of the sacrament, which becomes an unquestionable pastoral problem. However, does the lack of faith on the part of the person prevent him from entering into a valid marriage? In my opinion does not prevent, although such a situation cannot be ruled out in the event of the exclusion of the sacramental dignity of marriage